Picosecond to Nanosecond Manipulation of Excited-State Lifetimes in Complexes with an Fe-II to Ti(IV )Metal-to-Metal Charge Transfer: The Role of Ferrocene Centered Excited States - ALTUN, ZİKRİ (AMER CHEMICAL SOC, 2019)
Time-resolved transient absorption spectroscopy and computational analysis of D-pi-A complexes comprising Fe-II donors and Ti-IV acceptors with the general formula (Cp2Ti)-Cp-R(C(2)Fc)(2) (where RCp = Cp*, Cp, and Cp-MeOOC) and (Cp2Ti)-Cp-TMS(C(2)Fc)(C2R) (where R = Ph or CF3) are reported. The transient absorption spectra are consistent with an Fe-III/Ti-III metal-to-metal charge-transfer (MMCT) excited state for all complexes. Thus, excited-state decay is assigned to back-electron transfer (BET), the lifetime of which ranges from 18.8 to 41 ps. Though spectroscopic analysis suggests BET should fall into the Marcus inverted regime, the observed kinetics are not consistent with this assertion. TDDFT calculations reveal that the singlet metal-to-metal charge-transfer ((MMCT)-M-1) excited state for the Fe-II/Ti-IV complexes is not purely MMCT in nature but is contaminated with the higher-energy (1)Fc (d-d) state. For the diferrocenyl complexes, (Cp2Ti)-Cp-R(C(2)Fc)(2), the ratio of MMCT to Fc centered character ranges from 57:43 for the Cp* complex to 85:15 for the Cp-MeOOC complex. For the diferrocenyl and monoferrocenyl complexes investigated herein, the excited-state lifetimes decrease with increased (1)Fc character. The effect of Cu-I coordination was also analyzed by time-resolved transient absorption spectroscopy and reveals the elongation of the excited-state lifetime by 3 orders of magnitude to 63 ns. The transient spectra and TDDFT analysis suggest that the long-lived excited state in Cp2Ti(C(2)Fc)(2).CuX (where X is Cl or Br) is a triplet iron species with an electron arrangement of Ti-IV-Fe-3(II)-Cu-I.
Keywords: GENERALIZED GRADIENT APPROXIMATION; CORRELATED MOLECULAR CALCULATIONS; GAUSSIAN-BASIS SETS; ELECTRON-TRANSFER; PHOTOREDOX CATALYSIS; DENSITY FUNCTIONALS; REDOX CHEMISTRY; ENERGY-TRANSFER; SOLAR-CELLS; DYNAMICS